Pengaruh Brand Image Terhadap Customer Engagement Konsumen Starbucks di Kota Denpasar - Ni Kadek Dilasanthika; Putu Ratna Juwita Sari; Kadek Wulandari Laksmi P; Ni Kadek Winda Yanti (Penerbit Jurnal Indonesia, 2026)
The purpose of this study is to analyze the influence of brand image on customer engagement among Starbucks consumers in Denpasar City. This study used a quantitative approach with simple linear regression analysis. Data were obtained through questionnaires distributed to consumers who had made purchases at Starbucks and analyzed using a t-test and coefficient of determination. The results showed that brand image had a positive and significant effect on customer engagement (t = 2.827; Sig = 0.005) with an Adjusted R Square value of 0.759, meaning brand image was able to explain 75.9% of the variation in customer engagement, while the remaining 24.1% was influenced by other factors outside the study. Thus, it can be concluded that a strong brand image plays a significant role in increasing customer engagement among Starbucks consumers in Denpasar City and can be used as a basis for formulating the company's marketing strategy. These findings indicate that a positive brand image strengthens emotional attachment and interaction between consumers and the brand. A strong brand image encourages consumers to actively engage through repeat purchases, word-of-mouth communication, and interactions on digital platforms. Therefore, companies need to consistently maintain brand quality, brand communication, and brand experience to sustain customer engagement. This study also provides empirical evidence that brand image is a strategic asset in building long-term relationships with consumers.